2021
DOI: 10.3390/antiox10081183
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Salinity and Light Spectra Regulates Glucosinolates, Phenolics, and Antioxidant Capacity of Brassica carinata L. Microgreens

Abstract: The effect of salt treatment on Brassica carinata (BC) microgreens grown under different light wavelengths on glucosinolates (GLs) and phenolic compounds were evaluated. Quantifiable GLs were identified using ultra-high performance-quadrupole time of flight mass spectrometry. Extracts’ ability to activate antioxidant enzymes (superoxide dismutase (SOD) and catalase (CAT)) was evaluated on human colorectal carcinoma cells (HCT116). Furthermore, BC compounds’ ability to activate expression of nuclear transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 80 publications
2
19
0
Order By: Relevance
“…A total of 200 mg of finely ground powder of the various collected organs were prepared in triplicate, dissolved in 4 mL ethanol (70%), and extracted twice in a sonicator (Bandelin Sonorex, Berlin, Germany) set at 40 °C for 15 min each [ 13 ]. The extracts were centrifuged at 3000 RPM for 15 min at 4 °C and at a rotation radius of 325 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 200 mg of finely ground powder of the various collected organs were prepared in triplicate, dissolved in 4 mL ethanol (70%), and extracted twice in a sonicator (Bandelin Sonorex, Berlin, Germany) set at 40 °C for 15 min each [ 13 ]. The extracts were centrifuged at 3000 RPM for 15 min at 4 °C and at a rotation radius of 325 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Leafy vegetables, which account for a large portion of the global human diet, have been identified as a particularly rich and essential source of such metabolites [ 11 ]. Research shows that a high vegetable diet is associated with an improved total antioxidant status of blood and cellular antioxidant activities, as well as lower risks of associated diseases such as cardiovascular disease, whereas a low vegetable intake is associated with risks and predisposition to heart diseases [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, sweet basil (Ocimum basilicum) developed more fresh weight under a red/blue ratio of 2 or 3 units compared to 0.5, 1, and 4 units [28]. Mustard and kale microgreens reportedly had greater fresh weight under monochromatic blue compared to red/blue ratio of 1 [17], while the opposite result was observed in Brassica carinata microgreens [29]. Moreover, Gerovac et al [30] found greater fresh weight in mustard microgreens grown under red/green/blue (74/18/8%) compared to red/blue (87/13%) and red/blue/far-red (84/9/7%), while they did not find significant differences in the fresh weight of kohlrabi and mizuna microgreens.…”
Section: Morphologymentioning
confidence: 95%
“…Moreover, the activity of a major enzyme participating in the phenolic biosynthesis, phenylalanine ammonia lyase (PAL), is known to be regulated by light quality [41]. Brassica carinata microgreens produced greater amounts of phenolics when treated with monochromatic blue compared to red and 50% red/ 50% blue light [29]. As with the green basil used in this study, Lobiuc et al [42] found a higher phenolic content in green basil (Ocimum basilicum) under increased red light portion, while Gimenez et al [40] reported greater total phenolic content in purslane microgreens treated with red-blue light compared to fluorescence and red-blue, including far-red.…”
Section: Phytochemical Analysesmentioning
confidence: 99%
“…Light quality can be combined with other environmental conditions to optimize its impact on plants [21]. For instance, sprout characteristics depend on growth temperature [7].…”
Section: Introductionmentioning
confidence: 99%